Masa Keemasan Intelektual Islam: Studi Historis Pendidikan Islam pada Era Khalifah Al-Ma’mun - Fatimah Al Jahra; Salsabila Khairani; Mahfud Ifendi (Reflection : Islamic Education Journal, 2025)
This article is written to examine the golden age of Islamic intellectuals, focusing on the development of education during the era of Caliph al-Ma'mun (786–833 AD) of the Abbasid Dynasty, and to explore the factors underlying the progress of science during that period. The research method used is a literature study with a qualitative historical descriptive approach; data were collected through a review of primary and secondary sources (books, journals, historical documents), then analyzed systematically through the process of de-contextualization, coding, grouping, and re-contextualization in order to compile a comprehensive historical narrative. The results of the study indicate that al-Ma'mun's policies including the establishment of BaitulHikmah, the movement to translate foreign scientific works, and political and economic support created an open and inclusive intellectual climate, accelerating the development of science, philosophy, and formal education to the village level. The implications of these findings emphasize the importance of synergy between state support, political stability, and respect for diversity as a foundation for the development of modern educational institutions and cross-cultural knowledge exchange.